Knowledge-related iron deficiency anemia among undergraduate nursing female students in the University of Baghdad - Massara A. Najm; Ali Hussein Alek Al-Ganmi; Ahmed Fleih Hassan (Journal of Education and Health Promotion)
BACKGROUND: Globally, iron deficiency anemia is a problematic nutritional deficiency health-related issue that impacts early-adulthood people such as university students. The aim was to asses female nursing students’ knowledge concerning iron deficiency anemia in the College of Nursing, University of Baghdad. MATERIALS AND METHODS: A cross-sectional survey was carried out from the period of June 18, 2023 to December 20, 2023. Nonprobability (purposive) samples of 100 female nursing students were selected from the second, third, and fourth stages in the College of Nursing, University of Baghdad. Data collection included students’ sociodemographic characteristics, and students’ knowledge questionnaire consists of “20” constructed questions, which included the students’ knowledge about iron deficiency. The knowledge questionnaire has been developed through reading textbooks and review of the literature for the related topic. The data have been analyzed through the application of descriptive and inferential analysis and using SPSS version 26. RESULTS: The finding of the study revealed that the level of female students’ knowledge regarding iron deficiency anemia based on the total mean score of M(SD) = 1.33 (0.39) showed a poor level. Also, there is a significant association between students’ age and academic stage with their level of knowledge of iron deficiency anemia, P = 0.028. CONCLUSION: The female nursing students at the University of Baghdad had a poor level of knowledge about iron deficiency anemia, and this can be attributed to their academic stage in the College of Nursing. There is a significant association between students’ age and academic stage with their iron deficiency anemia knowledge. Faculty of nursing should increase female students’ health awareness and their understanding, knowledge, motivation, and perception regarding iron deficiency and how to prevent it.